Localization of sequences controlling the spatial, temporal, and sex-specific expression of the esterase 6 locus in Drosophila melanogaster adults. - Ludwig, M Z (1993)
The esterase 6 gene (Est-6) of Drosophila melanogaster is expressed in a variety of tissues that differ between larval and adult stages and among related species. Variability in the level of expression of this locus among different species and strains and its species- and tissue-specific patterns of expression make it a useful system for studying the evolution of gene regulation in Drosophila. We have begun to determine the location of the regulatory regions of Est-6 by constructing deletion mutants of the 5' regions of the gene and transforming them back into flies. Deletion mutants of the putative 5' promoter regions of Est-6 were fused to the bacterial beta-galactosidase gene (lacZ) and assayed for their ability to direct tissue-specific expression in transformed D. melanogaster adults. We have identified four independently acting Est-6 regulatory regions that direct the expression of lacZ in (i) the ejaculatory duct; (ii) the adult salivary glands; (iii) the respiratory system, prefrons, antennae, and maxillary palps; and (iv) the ejaculatory bulb and prefrons. We also found a region near the start of transcription that directed expression of Est-6 in the cardia or proventriculus in some transformed lines.